Multimodal data collection in Alzheimer's disease: Participant acceptance of various digital technologies employed in the MEDIA study. (20th December 2022) - Sorinas, Jennifer; Curcic, Jelena; Vallejo, Vanessa; Sverdlov, Oleksandr; Piksa, Mateusz; Erdemli, Gul; Praestgaard, Jens; Snædal, Jón; Cha, Jang‐Ho; Hannesdottir, Kristin; Team, MEDIA Study
Abstract: Background: The rate of failed drug trials in Alzheimer's disease (AD) remains high. Many conventional endpoints currently used to demonstrate success of clinical trials lack sensitivity to drug treatment effects and perform disparately across disease stages. These endpoints tend to be burdensome "single time‐point" assessments that are vulnerable to subjectivity and rater errors. Novel technologies are rapidly emerging at the same time as our understanding of how to optimally measure drug treatment effects is evolving. Rather than relying on reductionist paper‐pencil assessments, a multimodal approach incorporating more frequent and/or more direct physiological assessments, may result in better detection of true treatment effects. However, will such an approach add too much burden to clinical trials? Are elderly participants in AD trials willing and able to operate new technologies? It is clear that any endpoint that is not well‐accepted by sites or trial participants is unlikely to be successfully adopted for large clinical drug trials. Method: The MEDIA study was a single‐site study evaluating 10 digital in‐clinic assessments in 38 early AD participants and 12 cognitively healthy controls. The assessments included computerized and augmented reality assessments as well as wearable gait and EEG monitoring. This study additionally included conventional cognitive assessments augmented with unobtrusive digital sensors; such as eye tracking via a tablet camera, speech analytics using voice recordings and physiological assessments using a tablet or pen with built‐in sensors. All participants completed a feedback survey on each of the digital assessments. This feedback survey asked seven questions about ease of use, burden of the assessment and clinical meaningfulness. Responses were recorded on a scale of 0 = strongly disagree to 5 = strongly agree. Result: The results revealed overall good acceptance of the digital technologies. Although some of the assessments were considered mentally demanding, the majority of participants felt the technologies were easy to use, clinically meaningful and enjoyable. Conclusion: There is great anticipation for more sensitive clinical endpoints in AD. However, a question remains on the operational feasibility and how acceptable digital endpoints are to trial participants. This presentation discusses early AD participant (from presymptomatic to mild dementia) acceptance of different digital assessments.